2004
DOI: 10.1038/sj.gt.3302285
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of tumor metastasis by NK4 plasmid DNA released from cationized gelatin

Abstract: NK4, composed of the NH 2 -terminal hairpin and subsequent four-kringle domains of hepatocyte growth factor (HGF), acts as an HGF-antagonist and angiogenesis inhibitor. This study is an investigation to evaluate the feasibility of controlled release formulation of NK4 plasmid DNA in suppressing the tumor growth, and lung metastasis. Biodegradable cationized gelatin microspheres were prepared for the controlled release of an NK4 plasmid DNA. The cationized gelatin microspheres incorporating NK4 plasmid DNA coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 47 publications
1
50
0
Order By: Relevance
“…Our previuos study revealed that the injection of cationized gelatin microspheres incorporating NK4 plasmid DNA significantly inhibited angiogenesis in tumor tissue while increased the number of apoptotic tumor cells. 53 These findings are consistent with previous studies in which angiogenesis inhibitors suppressed the tumor growth through increasing apoptosis of tumor cells. 54,55 Thus, it is possible that NK4 suppresses primary tumor growth mainly through inhibition of tumor angiogenesis.…”
Section: Discussionsupporting
confidence: 83%
“…Our previuos study revealed that the injection of cationized gelatin microspheres incorporating NK4 plasmid DNA significantly inhibited angiogenesis in tumor tissue while increased the number of apoptotic tumor cells. 53 These findings are consistent with previous studies in which angiogenesis inhibitors suppressed the tumor growth through increasing apoptosis of tumor cells. 54,55 Thus, it is possible that NK4 suppresses primary tumor growth mainly through inhibition of tumor angiogenesis.…”
Section: Discussionsupporting
confidence: 83%
“…2,3 In spite of their high transduction efficiency, viral vectors are associated with immunogenicity, toxicity and possible mutagenesis of the target cells. 4 Non-viral vectors have become an attractive alternative, [5][6][7] but the low efficiency of transfection results in less efficient targeting of genes to the tissue of interest. The lack of an effective and safe gene targeting vector has become the major barrier to the wide application of gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…8 An aqueous solution of 10 wt % cationized gelatin (10 ml) was preheated at 40°C and then added dropwise into 375 ml of olive oil preheated at 40°C, while an impeller stirring at 420 rpm was used for 10 minutes to yield a water-in-oil emulsion. The emulsion temperature was decreased to 4°C followed by further stirring for 30 minutes for the natural gelation of gelatin aqueous solution.…”
Section: Preparation Of Cationized Gelatin Microspheresmentioning
confidence: 99%
“…The carboxyl groups of gelatin were chemically converted by introducing amino groups for cationization of gelatin. 8 Briefly, ethylenediamine and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride salt were added to 250 ml of 100 mmol/L PBS containing 5 g of gelatin. The molar ratio of ethylenediamine to the carboxyl groups of gelatin was 50.…”
Section: Preparation Of Cationized Gelatinmentioning
confidence: 99%
See 1 more Smart Citation